Tourism Business Planning in Enhancing the Role of the Young Generation Case Study: West Java Tourism Ambassador Selection Event 2022 - Fariz Fardani Nurbaihaqi; Nenden Yayu Destiana; Dewi Turgarini; Caria Ningsih (Budapest International Research and Critics University, 2022)
The West Java tourism ambassador is a talent search event in the tourism sector for the younger generation to contribute to economic improvement, introduce tourist attractions, and promote West Java tourism in the era of technological sophistication. This technology can facilitate the dissemination of information quickly, so the role of tourism ambassadors is needed as a driver who is expected to portray themselves well. The hope is that the tourism ambassador can encourage tourism growth in Indonesia, especially in West Java. The purpose of this research is to try to introduce and promote regional tourism, to become a means or forum for appreciation for tourism actors in West Java, to hone the potential of the younger generation according to their fields, as a place to compete so that they are trained to become figures who have the spirit to continue the process and take advantage of youth. With full achievements, cultivate an attitude of love for the region, train the younger generation to think creatively, be innovative, and become inspirational figures to inspire the wider community. The method used in this study is a qualitative descriptive method. Descriptive type the qualitative research used is a case study approach. The case study studied was the 2022 West Java Tourism Ambassador event held in March 2022 and is one of the activities designed by tourism consultants. Data collection was obtained through observation, financial analysis, and documentation analysis. This study found that tourism activities require assistance in planning by a tourism consultant in preparing activities, planning activity concepts, interesting Implementation, and evaluation after activities. Good and professional activity planning can positively impact the younger generation who participate in activities carrying out their role in society, especially in promoting tourism.